Training on the Pneumatic Work with Petroleum Patients within the Preliminary and Practical Way - Rejapova, Nodira (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the change in cotton density transmitted during pneumatic pipe transfer in time unit, ie irregularity of transmission, movement of the cotton lining to the pneumatic tube and the pipe movement and its movement in the piped wavy traverse and the collision with the pipe wall. In order to minimize negative impacts on cotton quality, it has been argued that it is best to transfer cotton at a reasonable rate, in the plain corresponding to the center of the pipe and at the same speed as the current flow rate.